Glycaemic Index of Commercially Available Brown Rice in East Coast of Peninsular Malaysia - Wan Rosli, W. I.; Wan Muda, Wan Abdul Manan; Abu Bakar, Nordiana; S. Malik, Vasanti; Willet, Walter C.; Hu, Frank B.; Ong , Mei Gee; Tengku Ismail, Tengku Alina; Abdul Jalil, Rohana (International Digital Organization for Scientific Information (IDOSI), 2016)
Rice is a staple routine food of huge world population including Malaysian. Two brown rice varieties commercially available in East Coast of Peninsular Malaysia were investigated for its Glycemix Index values (GI). The total dietary fiber contents of Long grain specialty 1 (LGS1) and Long grain specialty 2 (LGS2) were 4.19g and 4.79g/100g and significantly higher than white rice which had low dietary fiber (0.15g/100g). Both LS1 and LS2 brown rice samples had 21 % amylose content. The LS1 brown rice had GI value of 64±6.3 while LS2 had GI value of 72±6.6. The difference between mean iAUC of LS1 and LS2 was statistically significant (p=0.6). The iAUC value of LS1 was 110 mmol.min/L while iAUC value of LS2 was 127mmol.min/L. LS1 could be categorized as having Medium GI while the LS2 was found to have High GI values. The main factors which influence the GI value of rice are specifically the chemical properties such as amylose content and gelatinization process.LS1 could be categorized as having Medium GI while the LS2 was found to have high GI values.